2010
DOI: 10.4028/www.scientific.net/kem.443.742
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Complete Residual Stress Tensors in SOS Hetero-Epitaxial Thin Film Systems by the Technique of X-Ray Diffraction

Abstract: This paper investigates residual stress of epitaxial silicon film on SOS thin film systems. The emphasis was to develop a method to obtain accurately the complete residual stress tensors. It was found that using the multiple asymmetric X-ray diffraction method to measure strains in 13 [hkl] directions, the complete residual stress tensors can be determined reliably. The results were verified by both the Raman Backscattering and the substrate curvature methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…directions. The previous study of the authors has shown that in the SOS system, the three in-plane film stresses (i.e., σ 11 , σ 12 and σ 22 ) are much larger than the other stress components (i.e., σ 31 , σ 32 and σ 33 ) [12], which indicates that the stress state can be simplified to a plane-stress state. With sufficient numbers of d hkl , the intercept a 0 and variables σ 11 , σ 22 , and σ 33 could be solved using the least-square method from the linear equation set of…”
Section: Xrd Analysis Of Temperature-dependent Stressesmentioning
confidence: 98%
See 1 more Smart Citation
“…directions. The previous study of the authors has shown that in the SOS system, the three in-plane film stresses (i.e., σ 11 , σ 12 and σ 22 ) are much larger than the other stress components (i.e., σ 31 , σ 32 and σ 33 ) [12], which indicates that the stress state can be simplified to a plane-stress state. With sufficient numbers of d hkl , the intercept a 0 and variables σ 11 , σ 22 , and σ 33 could be solved using the least-square method from the linear equation set of…”
Section: Xrd Analysis Of Temperature-dependent Stressesmentioning
confidence: 98%
“…Although the least square algorithm has been well established to solve for the complete stress tensor of a single-crystalline thin film [11,12], the accuracy is influenced by the stress-free lattice constant a 0 . In theory, a 0 changes with temperature owing to the thermal expansion of the lattice.…”
Section: Xrd Analysis Of Temperature-dependent Stressesmentioning
confidence: 99%
“…(1), the six strain components are parameters to be calculated using least-square method if a sufficient number (more than six) of ε ΦΨ are obtained. To improve the measurement accuracy, we developed the XRD method to utilize the multiple diffraction peaks pertaining to high Miller index planes [9]. A non-linear regression analysis of the excessive information of the anisotropic elastic strains is then conducted.…”
Section: Direct Xrd Stress Measurements For Crystalline Layersmentioning
confidence: 99%
“…In order to determine a complete stress tensor in an SOS wafer, the measuring directions are limited by the crystallographic orientations of (hkl) planes that contribute to diffraction. Thus 3-axis sample alignments are required to adjust the measured (hkl) plane in the required direction [39]. This normally adds difficulties to the measurement process.…”
Section: Residual Stresses Characterizationmentioning
confidence: 99%